1997
DOI: 10.1021/es960857p
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon Assessment of Aerobic Petroleum Bioremediation in the Vadose Zone and Groundwater at an AS/SVE Site

Abstract: Radiocarbon ( 14 C) measurement from vadose zone air and groundwater is an alternative technique to quantitatively estimate aerobic microbial CO 2 production from petroleum mineralization. The objectives of this study were (1) to demonstrate the effectiveness of radiocarbon in providing direct quantified evidence of in situ aerobic petroleum hydrocarbon biodegradation from vadose zone CO 2 and groundwater DIC at a gasoline-contaminated site being remediated by an air sparging/soil vapor extraction (AS/ SVE) sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 16 publications
(42 reference statements)
2
28
0
Order By: Relevance
“…It is thus possible to estimate the proportion of the entire CO 2 pool (respired carbon) attributable to the contaminant. Using solely this proportion, fossil-hydrocarbon or industrial chemical oxidation at field sites has been confirmed [7][8][9][10][11][12][13] . This proportion of contaminant derived CO 2 can then be coupled with total CO 2 mineralization rate (all CO 2 collected per unit time and volume) to determine intrinsic contaminant mineralization rate.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…It is thus possible to estimate the proportion of the entire CO 2 pool (respired carbon) attributable to the contaminant. Using solely this proportion, fossil-hydrocarbon or industrial chemical oxidation at field sites has been confirmed [7][8][9][10][11][12][13] . This proportion of contaminant derived CO 2 can then be coupled with total CO 2 mineralization rate (all CO 2 collected per unit time and volume) to determine intrinsic contaminant mineralization rate.…”
Section: Introductionmentioning
confidence: 94%
“…Because very distinct isotopic signatures are available in carbon-based contaminants, carbon isotopes have been recently applied to understanding contaminant attenuation processes at field sites [5][6][7][8][9][10][11][12][13] . Stable carbon isotopes can be used to determine if a source is attenuating based on Rayleigh distillation kinetics (c.f.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With a half-life of approximately 5700 years, petroleum sources are radiocarbon-free and thus provide a definitive end-member when analyzed against photosyntheticbased carbon sources, which contain modern CO 2 from the atmosphere. The percentage modern carbon (pMC) of living photosynthetic biomass is approxiamtely 110% because of nuclear bomb tests, which peaked before 1965 (Aelion et al, 1997). In contrast, petroleum carbon and CO 2 derived from its biodegradation have no 14 C and are thus 0 pMC.…”
Section: Introductionmentioning
confidence: 99%
“…Radiocarbon analysis was able to confirm petroleum biodegradation. Radiocarbon was also used to survey groundwater contaminant degradation at a gasolinecontaminated site undergoing remediation with an air sparging/ soil vapor extraction system (Aelion et al, 1997). The CO 2 radiocarbon signature in the soil gas and groundwater-dissolved inorganic carbon suggested aerobic petroleum biodegradation produced 59-87% of the total CO 2 .…”
Section: Introductionmentioning
confidence: 99%